Enabling Entrepreneurial Choice - Agrawal, Ajay; Gans, Joshua S.; Stern, Scott (Management Science, 2021)
Entrepreneurs must choose between alternative strategies for bringing their idea to market. They face uncertainty regarding both the quality of their idea as well as the efficacy of each strategy. Although entrepreneurs can reduce this uncertainty by conducting tests, any single test conflates the signal of the efficacy of the particular strategy and the quality of the idea. Resolving this conflation requires exploring multiple strategies. Consequently, entrepreneurial choice is enhanced by finding ways to lower the cost of testing multiple strategies, receiving guidance as to the types of tests likely to reduce signal conflation, and optimally sequencing tests based on previous beliefs. This creates a role for judgment that may be provided by trusted third parties such as mentors and investors. We hypothesize that institutions that lower the cost of transmitting and aggregating judgment spur entrepreneurial performance. This paper was accepted by David Simchi-Levi, Special Section of Management Science: 65th Anniversary.